ALLERGIC RHINITIS: MODERN APPROACHES OF TREATMENT - Yu.G. Levina; L.S. Namazova-Baranova; R.M. Torshkhoeva; E.A. Vishneva; A.A. Alekseeva; K.E. Efendieva ("Paediatrician" Publishers LLC, 2010)
Allergic rhinitis (AR) is global problem of world health care system. Last 50 years the prevalence of AR increased. AR influences social life, sleeping, school progress and capacity for work. AR is frequently combined with bronchial asthma; it is able to induce exacerbation of asthma. The treatment of AR should be directed to the control of symptoms, prophylaxis of complications, improvement of sleeping and quality of life of patients and their parents. Intranasal corticosteroids are the drugs of choice in treatment of children with AR, these medications stop all symptoms of the disease including eyes symptoms.Key words: children, allergic rhinitis, intranasal corticosteroids, treatment.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(6):45-51)